Design and Implementation of an IoT-Based Electric Motor Vibration and Temperature Disruption Handling System - Aryo De Wibowo Muhammad Sidik; Ilman Himawan Kusumah; Anang Suryana; Edwinanto; Marina Artiyasa; Anggy Pradiftha Junfithrana (FIDELITY : Jurnal Teknik Elektro, 2020)
Faults in three-phase electric motors often occur in power plants. Unfortunately, the disturbances are unpredictable and reduce unit performance. This paper presents an Internet of Things (IoT) based intrusion handling system for secure and economic data communication in industrial fields. The build system can monitor and control with FLM (First Line Maintenance). FLM is a minor corrective maintenance activity carried out while the unit is operating with the provision of simple equipment. Device design and testing using the ESP8266 microcontroller module to obtain motor vibration, current, and temperature information for motor conditions supported by the application as a user interface. The result prevents further damage to the electric motor by adding an external fan and a grease pump that serves for additional engine cooling. This research contributes to improving the performance of the generator at PT. Indonesia Power UJP West Java II Palabuhanratu is one of the steam power plants in West Java, Indonesia